Peran Puskesmas Untuk Mencapai Universal Health Coverage di Indonesia: Literature Review - Nabila Erinaputri; Resa Listiani; Faza Duta Pramudyawardani; Novita Dwi Istanti (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Universal Health Coverage (UHC) is a health insurance system where every citizen has access to health services, both promotive, preventive, curative, rehabilitative, and palliative. Universal Health Coverage (UHC) not only provides protection for health services, but also provides financial protection to the community. Puskesmas is an effort to realize this, which provides health services with the main program of mandatory health efforts. However, health services at puskesmas still require a lot of leverage in achieving Universal Health Coverage (UHC). The purpose of this study is to analyze the role of puskesmas to achieve Universal Health Coverage (UHC). This research uses the Literature Review literature study method with Search engines used in literature searches, namely Google Scholar and journal databases such as Researchgate with the keywords Indonesia, Puskesmas, Universal Health Coverage (UHC). The criteria for articles used were based on publications published between 2019 and 2023. The results showed that the health service efforts of puskesmas in Indonesia still have to be improved to realize quality services in order to realize universal health coverage (UHC). Efforts to increase community empowerment are carried out through community empowerment in the independence of healthy living, maintaining, and improving health status. The conclusion of this study shows that improving services at puskesmas continues to be carried out through several capacity building, infrastructure and system improvements or updates as well as several programs with preventive, promotive, and community empowerment to achieve Universal Health Coverage (UHC).